Relación diámetro-peso y proporción cromática del erizo Lytechinus variegatus (Echinoidea: Toxopneustidae) en las islas de Margarita y Cubagua, Venezuela - Gómez-Gaspar, Alfredo (2003)
In Margarita and Cabagua Islands, Venezuela, the sea urchin Lytechinus variegatus is consumed as food but few studies concern its biology. Between January 1999 and September 2000, 25 localities of Margarita and Cubagua islands we visited to determinate the relationship between diameter and weight of living urchins according to their coloration green or white. A total of 5 066 urchins (3 421 captured in Margarita and 1 645 in Cubagua) were measured. There is no significant difference in the weight-diameter relations of green or white sea urchins of both islands. The weight-diameter equation is P = 0.00246 D2.52. Utilizing a quadrant (0.5 X 0.5 m) monthly samples of urchins living in a 2 m2 of surface were taken to estimate the abundance of the specimens according their color (N = 6 948 urchins). The green urchins were more abundant than the white urchins, in a 3:2 proportion.